SUATU KONSEP AWAL AKUNTABILITAS PENDIDIKAN YANG MANTAP DI ERA TEKNOLOGI INFORMASI (Terkait dengan Akreditasi Program Studi pada Lingkungan LPTK PTK) - Enjang Akhmad Juanda; Mukhidin - (Prosiding APTEKINDO, 2010)
Lives, especially here for educational management domain, as if automatically,mechanistically passes away. It seems that our routine jobs/ functions as if nearly exactly controlled,as if nearly without soul. Meanwhile outside demands to us directly or indirectly more and morechallenges. Furthermore, actually our environment facilities according to information technology moreand more exists and self perfecting.In daily educational practises, we as educational society and even our stakeholders arealmost dominantly immersed to routinity of existing life stream automatically. This condition affecting tosomething crucial in nature thus just forgotten. What is that? That is educational accountability,standing/ errecting educational accountability. With this kind of awaraness, in mind, and in turnfollowed by action, we hope we can approach to our effort to a peak performances condition.In this paper we tried to analyze the educational accountability elements related to informationtechnology era that assumed as can be created. This elements could be as artificial or as dailyhappening (elements), but in our ideas is in effort to enliven or to enacting it. Because the educationalaccountability as educational practician or conceptors in my point of view is our entail obligation. In thispaper generally, we tried to analyze diverse of existing facilities whether in software, hardware orbrainware as long as it can be regulated according to our possibility efforts and abilities.Keywords: ICT/TIK, accountability/akuntabilitas, ranking.